SIMULATION ANALYSIS OF IPMSM WITH THREE & FIVE LEVEL DCML INVERTER USING CBSVPWM TECHNIQUE - G. Sree Lakshmi; S. Kamakshaiah; G. Tulasi Ram Das (European Scientific Journal, ESJ, 2013)
In this paper a closed loop controller is designed to obtain the desired output torque, speed and stator phase current of interior permanent magnet synchronous motor (IPMSM) fed by a three & five level diode clamped inverter which is built using IGBTs (Insulated-gate Bipolar Transistors). The modulation technique used is Carrier Based Space Vector Pulse Width Modulation (CBSVPWM). The complex trigonometric calculations involved in conventional SVPWM techniques creates delay in computations and hence the drive response is weakened. Compared to the conventional SVPWM this method is simpler and avoids complex trigonometric calculations and reduced voltage and current harmonics. The model of IPMSM is established in Matlab-Simulink using the equations describing its dynamic behavior. Simulation and analysis is also carried out in Matlab-Simulink.